ASSESSMENT OF BUSINESS OPPORTUNITIES IN RURAL AREAS OF SELECTED STATES IN THE SOUTH-SOUTH ZONE OF NIGERIA - UDOM, Bassey; E. Ebenezer, AKPAN, (PT. Altin Riset Publishing, 2025)
This study aims to assess and map business opportunities in rural areas of several states in Nigeria's South-South zone, focusing on agribusiness, non-farm enterprises, cooperatives, information and communication technology, and formal and informal financial systems. The main objective of the study was to identify factors that support and constrain rural enterprise growth, and to provide contextualized policy recommendations for sustainable economic empowerment. The research method used a mixed approach with a combination of quantitative surveys, in-depth interviews, and field observations in rural communities in Delta, Bayelsa, Rivers, Cross River, Akwa Ibom, and Edo states. Data were analyzed using descriptive methods, SWOT analysis, and the theoretical frameworks of rural development, entrepreneurial ecosystems, and small towns theory. The results showed that the agribusiness sector, particularly cassava production, oil palm, and fisheries, has great potential but is constrained by market access, capital, and processing facilities. Non-farm businesses are growing as a diversification strategy, with women playing a significant role in petty trade and services. Cooperatives and informal financial systems such as Esusu are the main support for business capital, while access to formal banks remains limited. The potential for digitization through social media and digital banking services is emerging, although hampered by limited infrastructure and literacy. SWOT analysis confirmed that natural resources and local social networks are key strengths, while weak infrastructure and economic uncertainty are threats. Overall, this research emphasizes the need for an integrative approach that links local resources with institutional support and inclusive development policies to foster sustainable rural entrepreneurship in South-South Nigeria.